2011
DOI: 10.1371/journal.pone.0014818
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Acute Childhood Malnutrition during the National Nutrition Week in Mali Increases Treatment Referrals

Abstract: ObjectiveTo evaluate a pilot intervention designed to integrate mid-upper arm circumference (MUAC) screening for acute malnutrition into the semi-annual Child Nutrition Week (Semaine d'Intensification des Activités de Nutrition, or “SIAN”) activities carried out in June 2008.DesignA cross-sectional survey was conducted in Kolokani and Nara, two health districts in the Koulikoro region of Mali, 4–5 months after the SIAN, using a population-proportionate, multi-stage random sample of: 1) health centers, and 2) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The difference in screening coverage was substantial: 52% of eligible children (those in the 6–59-month age range) were screened during the event, compared with 22% screened at health centers and 5% screened in the community in the months following the event. 28 The discrepancies in screening rates suggest that both facility and community-based SAM screening have considerable room for improvement: half of the children with acute malnutrition in their survey had been at a health center within the previous 4 months, but only a quarter of them had been assessed for malnutrition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in screening coverage was substantial: 52% of eligible children (those in the 6–59-month age range) were screened during the event, compared with 22% screened at health centers and 5% screened in the community in the months following the event. 28 The discrepancies in screening rates suggest that both facility and community-based SAM screening have considerable room for improvement: half of the children with acute malnutrition in their survey had been at a health center within the previous 4 months, but only a quarter of them had been assessed for malnutrition.…”
Section: Resultsmentioning
confidence: 99%
“…This may partially explain why screening rates and detection of SAM cases remain low even at clinics where staff have been trained in CMAM protocols. 28 If the findings by Blackwell et al (2015) hold true, further simplifying the MUAC protocol may address issues of familiarity and understanding of MUAC among health care providers and caregivers alike. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary foods, personnel and infrastructure each contributed an important proportion to total MAM treatment costs, but none materially influenced conclusions regarding the overall cost-effectiveness of MAM treatment. Community-based screening, which has the potential to promote early case finding and increase treatment referrals,25 represented a relatively small sum in the management of acute malnutrition. Greater investment in increasing screening frequency or improving screening efficiencies, such as through increased community mobilisation, could increase programme coverage, reduce per-capita fixed costs associated with treatment and prevent the more costly management of complicated cases.…”
Section: Discussionmentioning
confidence: 99%
“…In Mali, a survey listed the low coverage of screening for AM as an important barrier to adequate CMAM treatment coverage [14]. Also in Mali, another study found that over a 4- to 5-month period, only 22% of children were screened by CHVs and 5% by health center staff [15]. These findings stress the need to boost screening coverage and increase caregivers’ knowledge and awareness of AM and of the existing local CMAM services.…”
Section: Introductionmentioning
confidence: 99%